Proteomic Responses Under Cold Stress Reveal Unique Cold Tolerance Mechanisms in the Pacific White Shrimp (Litopenaeus vannamei) - Peng, Jin-Xia; He, Ping-Ping; Wei, Pin-Yuan; Zhang, Bin; Zhao, Yong-Zhen; Li, Qiang-Yong; Chen, Xiu-Li; Peng, Min; Zeng, Di-Gang; Yang, Chun-Ling; Chen, Xiaohan (Frontiers in Physiology, 2018)
The Pacific white shrimp (Litopenaeus vannamei), one of the most widely cultured shrimp species in the world, often suffers from cold stress. To understand the molecular mechanism of cold tolerance in Pacific white shrimp, we conducted a proteomic analysis on two contrasting shrimp cultivars, namely, cold-tolerant Guihai2 (GH2) and cold-sensitive Guihai1 (GH1), under normal temperature (28°C), under cold stress (16°C), and during recovery to 28°C. In total, 3,349 proteins were identified, among which 2,736 proteins were quantified. Based on gene ontology annotations, differentially expressed proteins largely belonged to biological processes, cellular components, and molecular functions. KEGG pathway annotations indicated that the main changes were observed in the lysosome, ribosomes, and oxidative phosphorylation. Subcellular localization analysis showed a significant increase in proteins present in cytosol, extracellular regions, and mitochondria. Combining enrichment-based clustering analysis and qRT-PCR analysis, we found that glutathione S-transferase, zinc proteinase, m7GpppX diphosphatase, AP2 transcription complex, and zinc-finger transcription factors played a major role in the cold stress response in Pacific white shrimp. Moreover, structure proteins, including different types of lectin and DAPPUDRAFT, were indispensable for cold stress tolerance of the Pacific white shrimp. Results indicate the molecular mechanisms of the Pacific white shrimp in response to cold stress and provide new insight into breeding new cultivars with increased cold tolerance.